Meningkatkan Pemahaman Kaidah Ilmu Nahwu Melalui Penerapan Rumus Arab Pegon di Majlis Ta’lim Nurul Ilmi Desa Ciracas - Fauzi, Abdul Rahmat; Enjang, Enjang; Luthfi, Taufik (Universitas Galuh, 2024)
Learning the rules of nahwu science with the pegon Arabic formula method is still rarely found in educational institutions that study Arabic literature in Indonesia. This community service program at majlis ta'lim nurul ilmi aims to improve the skills and understanding of students in teaching the rules of nahwu science. This education-based community development service was carried out at Majlis Ta'lim Nurul Ilmi Ciracas Village with the involvement of 13 students as partner subjects. Through a series of introductions, learning, training and mentoring sessions, this program introduces the pegon Arabic formula method in understanding the rules of nahwu science. The results showed a significant increase in the level of understanding of students towards understanding the rules of nahwu science. The positive impact is also seen in the creativity and activeness of the students in the lessons of nahwu science rules. The program is innovative in its scholarly integration and collaborative approach between academics and practitioners. Based on the results, it is recommended to implement similar programs in other Educational Institutions with variations in context. This program highlights the importance of training students in developing the pegon Arabic formula method and preparing students for a competitive future